2016
DOI: 10.7567/jjap.55.05fj06
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of amber light-emitting diodes based on InGaN/AlN/AlGaN quantum wells

Abstract: We investigated InGaN-based amber light-emitting diodes (LEDs) with AlN/(Al)GaN barrier layers grown by metalorganic vapor-phase epitaxy. Tensilely strained AlN/Al0.03Ga0.97N barriers improved the crystalline quality of compressively strained InGaN quantum wells. We found that strain compensation among wells and barriers improves the external quantum efficiency of high-In-content InGaN-based amber LEDs. The amber LEDs with AlN/Al0.03Ga0.97N barriers have shown an electroluminescence (EL) intensity approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…InGaN red LEDs exhibited increasing characteristic temperatures with increasing current densities suggesting that the nonradiative recombination centers play a key role in the total recombination. This phenomenon originated from the material quality and its LEDs [24,29,34,230,231] was smaller than that of AlGaInP ones [232,233] (see Figure We also observed that the redshift coefficient reduced when the current density increased. The energy distribution of carriers at a high current density could be increased due to heat generation by a non-radiative recombination process [132], which mostly corresponded to a broadening of emission spectra toward the high energy side according to Chhajed et al [229].…”
Section: Temperature Stabilitiesmentioning
confidence: 85%
See 1 more Smart Citation
“…InGaN red LEDs exhibited increasing characteristic temperatures with increasing current densities suggesting that the nonradiative recombination centers play a key role in the total recombination. This phenomenon originated from the material quality and its LEDs [24,29,34,230,231] was smaller than that of AlGaInP ones [232,233] (see Figure We also observed that the redshift coefficient reduced when the current density increased. The energy distribution of carriers at a high current density could be increased due to heat generation by a non-radiative recombination process [132], which mostly corresponded to a broadening of emission spectra toward the high energy side according to Chhajed et al [229].…”
Section: Temperature Stabilitiesmentioning
confidence: 85%
“…where I is the EL intensity, IT=RT is the EL intensity at room temperature (RT), T [K] is the temperature of the sampling stage, and Tch [K] is the characteristic temperature. The [24,29,34,217,230,231]. For comparison, we also plot the characteristic temperatures of AlGaInP-based LEDs [232,233].…”
Section: Temperature Stabilitiesmentioning
confidence: 99%
“…Due to their larger piezoelectric field, yellow−orange−red InGaN-based LEDs are particularly prone to such color variation. 7,31) Interestingly, the color correlated temperature (CCT) of white LEDs is also affected when varying their driving current. In this case, it is the efficiency of the phosphor conversion which decreases at higher current density and causes the CCT to drift toward cooler hues.…”
Section: Color Mixing Investigationmentioning
confidence: 99%
“…The large energy gap of nitride semiconductors is used for optoelectronic purposes. Especially the InGaN alloy is suitable for light emitter diode into the blue , green , yellow , amber , and violet range. Lasers and solar cells also are possible device applications .…”
Section: Introductionmentioning
confidence: 99%